Slavery and Freedom in the Epistle to the Galatians - Mario Kushner (Kairos (English Ed.), 2011)
This article surveys the Pauline teaching in the Epistle to the Galatians of the status of Christians before and after their conversion as it fits the imagery of slavery, as is often used in the New Testament. The first section deals with the pre-salvation status of Paul’s readers and their slavery to Satan. The second section describes their release from that slavery into freedom. The final section shows the limits of that freedom by describing the post-salvation status of Paul’s audience.